Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2022 - Kögler, Kristina; Weyland, Ulrike; Kremer, Hugo H. (Schriftenreihe der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2022)
The Yearbook of Vocational Education 2021 provides an overview of the current state of relevant research. It corresponds with the broad thematic and methodological range of research and theory development in vocational education.